EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBASIS ARTIFICIAL INTELLIGENCE-SLIDESGO UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Mochamad Guntur; Amara Salsabilla; Siti Sahronih; Herisa Hardiyanti Sholeha (Program Studi PGSD Universitas Flores, 2025)
This study aims to examine the effectiveness and impact of the Problem Based Learning (PBL) model based on AI-Slidesgo on the mathematical problem-solving abilities of 5th-grade students at SD Negeri 1 Tuk and SD Negeri 1 Dawuan Cirebon for the 2023/2024 academic year. The effectiveness of this study is demonstrated by the increase in the average problem-solving ability of students in the 4 experimental classes, and the impact of this study is shown by the difference in the average problem-solving ability of students in the 4 experimental classes. This research is a quantitative study. Data collection techniques using interviews, tests, questionnaires, and documentation. The sample in this study consisted of 120 students. The collected data were analyzed using effectiveness test statistical analysis, namely the t-test and n-gain test. Hypothesis testing shows that the t-test results indicate a significant result < 0.005, which means there is an improvement in students' mathematical problem-solving abilities. The n-gain test results show a gain in experimental class A of 0.65 with a moderate category; experimental class B 0.66 with a moderate category; experimental class C 0.81 with a high category, and experimental class D 0.73 with a high category. The results of the MANOVA test showed a significance value of 0.000, where 0.000 < 0.05, indicating that the PBL model and slidesgo-based learning media have an effect on students' mathematical problem-solving abilities.